2009
DOI: 10.4049/jimmunol.0803463
|View full text |Cite
|
Sign up to set email alerts
|

Alternatively Activated Macrophages Elicited by Helminth Infection Can Be Reprogrammed to Enable Microbial Killing

Abstract: The prime function of classically activated macrophages (activated by Th1-type signals, such as IFN-γ) is microbial destruction. Alternatively activated macrophages (activated by Th2 cytokines, such as IL-4 and IL-13) play important roles in allergy and responses to helminth infection. We utilize a murine model of filarial infection, in which adult nematodes are surgically implanted into the peritoneal cavity of mice, as an in vivo source of alternatively activated macrophages. At 3 wk postinfection, the perit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
116
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 73 publications
1
116
0
1
Order By: Relevance
“…In these systems, the Th2-driven, chronic stage of infection is characterized by the presence of alternatively activated macrophages indicated by the IL-4-dependent expression of fizz1 and ym1 [7,9,27,29,46]. Recently, Mylonas et al [47] have used these in vivo models of parasite infection to demonstrate further the plasticity of macrophage activation. This study has shown that even after long-term exposure to Th2 cytokines, macrophages could still respond to LPS and IFN-g stimulation to become antimicrobial in function.…”
Section: Discussionmentioning
confidence: 99%
“…In these systems, the Th2-driven, chronic stage of infection is characterized by the presence of alternatively activated macrophages indicated by the IL-4-dependent expression of fizz1 and ym1 [7,9,27,29,46]. Recently, Mylonas et al [47] have used these in vivo models of parasite infection to demonstrate further the plasticity of macrophage activation. This study has shown that even after long-term exposure to Th2 cytokines, macrophages could still respond to LPS and IFN-g stimulation to become antimicrobial in function.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings confirm and extend earlier studies on LPS 7-10,33,34 and staphylococcal enhancement of proinflammatory cytokine release by IL-4-pretreated M⌽s, with altered gene expression and signal transduction. 7 Interestingly, Mylonas et al 35 showed that nematodeelicited peritoneal M⌽s, which display IL-4-dependent features, secrete more proinflammatory cytokines in response to LPS/IFN-␥ challenge. The investigators also demonstrated that IL-4 priming of uninfected ThioM⌽s did not modify cytokine secretion after LPS/IFN-␥ stimulation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with recent evidence that, despite long-term exposure to Th2 cytokines in vivo, M⌽s could respond to Th1 stimuli and display a classically activated phenotype. 35 Moreover, Hagemann et al 50 demonstrated that tumor-promoting alternatively activated M⌽s can be reprogrammed to promote tumor killing. Our data confirm that highly polarized M⌽s maintain remarkable plasticity in their microenvironment.…”
Section: Il-4 Modulates Macrophage Response To Pathogens 359mentioning
confidence: 99%
“…Relm-a is a hallmark signature gene of murine alternatively activated macrophages (22)(23)(24)(25). However, we (and others) recently showed that intestinal epithelial cells and eosinophils can also express Relm-a (19,23,26).…”
mentioning
confidence: 99%